Fractal phototherapy: impact on the structure and function of the retina of rabbits with modelled retinal pigment epithelium atrophy - D. V. Fadeev; N. V. Neroeva; M. V. Zueva; I. V. Tsapenko; V. I. Kotelin; T. A. Pavlenko; O. V. Beznos; T. D. Okhotsimskaya; P. A. Ilyukhin; Yu. S. Timofeev (Российский офтальмологический журнал)
It is believed that in degenerative diseases of the retina, photostimulation by fractal dynamics signals activates neuroplasticity, thereby increasing the efficiency of visual rehabilitation. Previously, we showed a positive effect of fractal phototherapy (FF) on the electroretinogram (ERG) of healthy rabbits and demonstrated the safety of long-term photostimulation courses for the retina. The purpose of this work is to study the effect of FF on the functional activity and morphology of the retina in rabbits with a model of retinal pathology. Material and methods. We modelled an atrophy of retinal pigment epithelium (RPE) on both eyes of 50 rabbits. 30 days after the administration of bevacizumab, the animals were divided into two groups of 25 animals each. In the main group, photostimulation was performed using a device for FF, while in the control group incandescent lamps were used that create radiation of constant intensity. In both groups, 20-minute binocular light stimulation sessions were performed daily, five times a week. ERG and optical coherence tomography of the retina were performed before and after courses of treatment which lasted 1 week, 1 and 3 months. Results. Long-term courses of FF were shown to be safe for the morphology of the retina of animals with the RPE atrophy model. In all periods of observation, biochemical studies revealed no statistically significant changes in the content of norepinephrine and dopamine in the tear as compared with baseline values. In the main group, a slight positive effect of FF on rod and cone ERG was found after 5 FF sessions, while a significant increase in the amplitude of the transient and steady-state pattern-ERG (PERG), most pronounced after a 1-month FF course, was observed. Conclusions. A positive effect of FF on the functional activity of retinal ganglion cells (RGC) may suggest that prescribing a course of FF lasting up to 1 month (20 sessions) in diseases accompanied by a pathology of RGC is advisable, whereas for patients with a pathology of the macular region, such as AMD, an effective improvement in the activity of photoreceptors and bipolar cells could probably be achieved through a 1-week course of FF, conducted under the control of electroretinography.